2011
DOI: 10.5539/elt.v4n3p158
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Verb Noun Collocations in Writing Stories among Iranian EFL Learners

Abstract: An important aspect of native speakers' communicative competence is collocational competence which involves knowing which words usually come together and which do not. This paper investigates the possible relationship between knowledge of collocations and the use of verb noun collocation in writing stories because collocational knowledge distinguishes native speakers and foreign language learners and is a significant factor in productive skills especially writing. This study examined the correlation between kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
1
13
1
3
Order By: Relevance
“…frequency of accurately produced collocations recorded in student English), and English writing fluency. There are other studies which focus on the development and relationship between collocations and the productive language, especially writing (Al-Zahrani, 1998;Bazzaz & Samad, 2011;Hsu, 2002Hsu, , 2007. Al-Zahrani's findings are different from this study because Al-Zahrani did not take into account the use of verb-noun collocations, thus the frequency of verb-noun collocations in the Writing Test was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…frequency of accurately produced collocations recorded in student English), and English writing fluency. There are other studies which focus on the development and relationship between collocations and the productive language, especially writing (Al-Zahrani, 1998;Bazzaz & Samad, 2011;Hsu, 2002Hsu, , 2007. Al-Zahrani's findings are different from this study because Al-Zahrani did not take into account the use of verb-noun collocations, thus the frequency of verb-noun collocations in the Writing Test was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers discussed the relationship between collocations and the productive language, especially writing (Al-Zahrani, 1998;Bazzaz and Samad 2011;Farghal & Al-Hamly, 2007;Hsu, 2002;Zhang, 1993). Zhang (1993) was the first to study the correlation between knowledge and the use of collocations and the quality of collocations in 30 native and 30 non-native Indiana University of Pennsylvania freshmen .Al-Zahrani's study did not follow Zhang's because Al-Zahrani did not consider the use of collocations.…”
Section: Written Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the mentioned studies, Bazzaz and Samad (2011) discussed the relationship between collocational proficiency and the use of verb-noun collocations in writing stories since collocational proficiency differentiates native speakers and foreign or second language learners and is a major issue in productive skills especially writing. To this end, twenty seven Iranian PhD students in a Malaysian university were selected.…”
Section: Collocation Studies In Iranmentioning
confidence: 99%
“…The aforementioned studies in Iran discuss the different collocational proficiency of students and language proficiency; however their results are contradictory because some found that students' collocational proficiency improve as their language proficiency increases such as Bazzaz and Samad (2011), Ganji (2012) and Keshavarz and Salimi's (2007) while the others indicate that there is no relationship between collocational proficiency and language proficiency like Shokouhi and Mirsalari(2010) and Morshali (1995). Other studies worked on language transfer from L1 and found out that students use collocations incorrectly because of negative transfer and lack of exposure (Koosha and Jafarpour, 2006;Sadeghi, 2009;&Tajalli, 1994).…”
Section: Collocation Studies In Iranmentioning
confidence: 99%